Reconceptualizing Non-Cognitive Skills as Drivers of 21ST Century Competencies in Islamic Education: A Literature-Based Analysis - Helmi Handoko; Meli Puspita; Muhammad Sairozi (Jurnal Cendekia Media Komunikasi Penelitian dan Pengembangan Pendidikan Islam, 2026)
This study aims to reconceptualize non-cognitive skills as key drivers of 21st-century competencies by clarifying their definitions, analyzing their role in adaptive success, and formulating practical recommendations for Islamic Religious Education. This article contributes by offering a synthesized conceptual framework that positions non-cognitive skills as integrative drivers linking cognitive abilities and 4C competencies, addressing the conceptual fragmentation found in previous studies. This research employs a library research design with qualitative descriptive analysis. Data sources were selected based on relevance and credibility, including scholarly articles, policy documents, and prior studies. The analysis was conducted through thematic categorization and conceptual synthesis to identify key patterns and relationships. The findings indicate that non-cognitive skills encompassing intrapersonal aspects (motivation, resilience, self-regulation) and interpersonal aspects (communication, collaboration) serve as foundational enablers that optimize cognitive performance and support the development of 4C skills. The study also highlights their strategic role within the perspectives of Social Cognitive Theory and Human Capital Theory. The implications suggest that Islamic Religious Education should integrate non-cognitive skill development systematically into curriculum, pedagogy, and school culture. Practical recommendations include the implementation of Social-Emotional Learning, project-based learning, and growth mindset-oriented practices to enhance students’ character, adaptability, and holistic competencies in the 21st century.